2021
DOI: 10.1111/evo.14229
|View full text |Cite
|
Sign up to set email alerts
|

Testing the occurrence of convergence in the craniomandibular shape evolution of living carnivorans*

Abstract: Convergence consists in the independent evolution of similar traits in distantly related species. The mammalian craniomandibular complex constitutes an ideal biological structure to investigate ecomorphological dynamics and the carnivorans, due to their phenotypic variability and ecological flexibility, offer an interesting case study to explore the occurrence of convergent evolution.Here, we applied multiple pattern-based metrics to test the occurrence of convergence in the craniomandibular shape of extant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 100 publications
(206 reference statements)
2
20
0
Order By: Relevance
“…Additionally, mandible morphology has been shown to be evolutionarily more plastic, reflecting dietary adaptations more accurately than the cranium, whose morphological evolution must respond to conflicting functional demands 23 25 . However, in the last decades, the consolidation of geometric morphometric methods has resulted in an increase in this type of study, which have revealed that mandible shape (i.e., all its geometric features except for size, position, and orientation) in carnivorans is not only related to function (i.e., mastication), but to a complex interaction of factors such as evolutionary history, body size, sexual dimorphism, diet and, in carnivorous species, prey size 16 , 23 , 26 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mandible morphology has been shown to be evolutionarily more plastic, reflecting dietary adaptations more accurately than the cranium, whose morphological evolution must respond to conflicting functional demands 23 25 . However, in the last decades, the consolidation of geometric morphometric methods has resulted in an increase in this type of study, which have revealed that mandible shape (i.e., all its geometric features except for size, position, and orientation) in carnivorans is not only related to function (i.e., mastication), but to a complex interaction of factors such as evolutionary history, body size, sexual dimorphism, diet and, in carnivorous species, prey size 16 , 23 , 26 31 .…”
Section: Introductionmentioning
confidence: 99%
“…θ ranges from 0°to 180°, with lower values indicating convergence. Tamagnini et al (2021) calculated these based on a shared state (diet) expected to cause convergence. This involves calculating θ and phylogenetic distance (p) for each pair of taxa with that state.…”
mentioning
confidence: 99%
“…All three of these methods rely on novel estimates of ancestral states and were conceived within the last decade. Tamagnini et al (2021) contribute to a growing trend of applying phylogenetic comparative analyses to investigate historically qualitatively described phenomena. Tamagnini et al's (2021) findings that convergence is uncommon on the ordinal level but not too rare on the species level indicate the importance of taxonomic scale and demonstrate that interactions between biomechanics, ecology, and morphology are more nuanced than dietary categorizations.…”
mentioning
confidence: 99%
See 2 more Smart Citations